Changes at a Critical Branchpoint in the Anthocyanin Biosynthetic Pathway Underlie the Blue to Orange Flower Color Transition in Lysimachia arvensis - Sánchez-Cabrera, Mercedes; Jiménez-López, Francisco Javier; Narbona, Eduardo; Arista, Montserrat; Ortiz, Pedro L.; Romero-Campero, Francisco J.; Ramanauskas, Karolis; Igić, Boris; Fuller, Amelia A.; Whittall, Justen B. (Frontiers in Plant Science, 2021)
Anthocyanins are the primary pigments contributing to the variety of flower colors among angiosperms and are considered essential for survival and reproduction. Anthocyanins are members of the flavonoids, a broader class of secondary metabolites, of which there are numerous structural genes and regulators thereof. In western European populations of Lysimachia arvensis, there are blue- and orange-petaled individuals. The proportion of blue-flowered plants increases with temperature and daylength yet decreases with precipitation. Here, we performed a transcriptome analysis to characterize the coding sequences of a large group of flavonoid biosynthetic genes, examine their expression and compare our results to flavonoid biochemical analysis for blue and orange petals. Among a set of 140 structural and regulatory genes broadly representing the flavonoid biosynthetic pathway, we found 39 genes with significant differential expression including some that have previously been reported to be involved in the transition from blue to red-orange flowers. In particular, F3'5'H and DFR, two genes at a critical branchpoint in the ABP for determining flower color, showed differential expression. The expression results were complemented by careful examination of the SNPs that differentiate the two color types for these two critical genes. The decreased expression of F3'5'H in orange petals and differential expression of two distinct copies of DFR, which also exhibit amino acid changes in the color-determining substrate specificity region, strongly correlate with the blue to orange transition. Our biochemical analysis was consistent with the transcriptome data indicating that the shift from blue to orange petals is caused by a change from primarily malvidin to largely pelargonidin forms of anthocyanins. Overall, we have identified several flavonoid biosynthetic pathway loci likely involved in the shift in flower color in L. arvensis and even more loci that may represent the complex network of genetic and physiological consequences of this flower color polymorphism.